Evaluasi Kondisi Eksisting Program Desa/Kelurahan Berseri dan Perumusan Rekomendasi Peningkatan Kategori di Desa Betiting, Kabupaten Gresik - Putri, Fanny Amelia; Mirwan, Mohamad (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study examines how the Desa/Kelurahan Berseri Program, regulated by East Java Governor Regulation No. 56 of 2023, is implemented in Betiting Village, Gresik. The purpose of this study is to evaluate the existing conditions and develop a strategy for upgrading the category from Pratama to Madya using gap identification and SWOT analysis. Using a descriptive-evaluative approach and official 2025 assessment data, the results show that although the Pratama status has been achieved with a sufficient foundation, as an effort to upgrade the category from Pratama to Madya, the study suggests methods such as intensive household assistance, program replication, and optimization of communal wastewater treatment plants.